Pengaruh Pijat Bayi Terhadap Durasi Menyusu pada Bayi Usia 0–6 Bulan Di Klinik Wanasari Medika Karawang - Natalia Natalia; Rahayu Khairiah (Wellness And Healthy Magazine, 2022)
Background: The duration of breastfeeding that is less than optimal will cause malnutrition which causes the baby to be thin or even malnourished. The prevalence of nutritional status based on the weight index for age (W/U) in under-fives from the 2016 Indonesia Health Profile data, obtained the percentage of bad nutrition is 3.4%, malnutrition is 14.4%. In 2017 also did not differ much from 2016 with the percentage of malnutrition in children under five in Indonesia was 3.8%, undernutrition was 14%. Data from the results of the Basic Health Research (RISKESDAS) in 2018, there are 3.9% of malnutrition and 13.8% of malnutrition. Objective: This study aims to determine the effect of baby massage on the duration of breastfeeding in infantsaged 0-6 months. Methods: This study uses a time design with a comparison group. Data were collected using a checklist sheet. The research sample used was 50 people. The data analysis technique used independent sample t-test. Result: The resultsofthe t-testindicate that t-statvalueof 6.934 with a p-value (0.000) lessthan 0.05, so the decision taken was to accept Ha. This means that baby massage has an effect on the duration of breastfeeding at the Wanasari Medika Clinic, Karawang. The average in crease in breastfeeding duration in the group of infants who were not given massage was 1.48 minutes. While the group of infants who were given massage had anaverage in crease of 4.84 minutes. Conclusions and Suggestions: there is effect of baby massage on the duration of breastfeeding in infants aged 0-6 months. Socialization or campaigns about baby massage need to be carried out by them aternity clinic in order to improve the quality of breastfeeding in infants considering the benefits of massage in increasing the duration of breastfeeding in infants. Abstrack:  Latar Belakang: Durasi menyusui yang kurang optimal akan mengalami kekurangan gizi yang menyebabkan bayi kurus atau bahkan gizi buruk. Prevalensi status gizi berdasarkan indeks berat badan menurut umur (BB/U) pada balita dari data Profil Kesehatan Indonesia tahun 2016, didapatkan persentase gizi buruk sebesar 3,4%, gizi kurang sebesar 14,4%.  Pada tahun 2017 juga tidak berbeda jauh dari tahun 2016 dengan persentase gizi buruk pada balita di Indonesia adalah 3,8%, gizi kurang adalah 14%. Data dari hasil Riset Kesehatan Dasar (RISKESDAS) tahun 2018, terdapat 3,9% gizi buruk dan 13,8% gizi kurang. Tujuan: Untuk mengetahui pengaruh pijat bayi terhadap durasi menyusui pada bayi usia 0-6 bulan. Metode: Penelitian ini menggunakan rancangan waktu dengan kelompok pembanding. Data dikumpulkan menggunakan lembar checklist. Sampel penelitian yang digunakan adalah 50 orang. Teknik analisis data menggunakan uji t independent sample. Hasil:  Hasil uji t menunjukkan nilai t-hitung 6,934 dengan nilai p (0,000) kurang dari 0,05, sehingga keputusan yang diambil adalah menerima Ha. Artinya pijat bayi berpengaruh terhadap durasi menyusu di Klinik Wanasari Medika Karawang. Rata-rata peningkatan durasi menyusui kelompok bayi yang tidak diberikan pijat 1,48 menit. Sedangkan kelompok bayi yang diberikan pijat memiliki rata-rata peningkatan sebesar 4,84 menit. Kesimpulan dan Saran: pijat bayi berpengaruh terhadap durasi menyusu di Klinik Wanasari Medika Karawang. Sosialisasi atau kampanye tentang pijat bayi perlu dilakukan oleh pihak klinik bersalin dalam rangka meningkatkan kualitas menyusu pada bayi meningat adanya manfaat pijat dalam meningkatkan durasi menyusu pada bayi.